9x-3=2(4x+4)-5

Simple and best practice solution for 9x-3=2(4x+4)-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-3=2(4x+4)-5 equation:


Simplifying
9x + -3 = 2(4x + 4) + -5

Reorder the terms:
-3 + 9x = 2(4x + 4) + -5

Reorder the terms:
-3 + 9x = 2(4 + 4x) + -5
-3 + 9x = (4 * 2 + 4x * 2) + -5
-3 + 9x = (8 + 8x) + -5

Reorder the terms:
-3 + 9x = 8 + -5 + 8x

Combine like terms: 8 + -5 = 3
-3 + 9x = 3 + 8x

Solving
-3 + 9x = 3 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-3 + 9x + -8x = 3 + 8x + -8x

Combine like terms: 9x + -8x = 1x
-3 + 1x = 3 + 8x + -8x

Combine like terms: 8x + -8x = 0
-3 + 1x = 3 + 0
-3 + 1x = 3

Add '3' to each side of the equation.
-3 + 3 + 1x = 3 + 3

Combine like terms: -3 + 3 = 0
0 + 1x = 3 + 3
1x = 3 + 3

Combine like terms: 3 + 3 = 6
1x = 6

Divide each side by '1'.
x = 6

Simplifying
x = 6

See similar equations:

| 9y-20=-83+2y | | x^5-10x^4+25x^3-10r^2+24r=0 | | 6y+3=61 | | -16t^2+64t-36=0 | | 9t-17=-66+2t | | 15(v+1)-3v=3(4v+1)-4 | | X^3-6x+1=0 | | 0.05*1700,000-98.45= | | -2(3y+6)= | | 9r=4t+2 | | 0.05*1.7-98.45= | | 11x-7+3x-3=10x-4+3x | | 0.10(x+80)+0.30x=12 | | g(x)=2x^2+5x-1 | | g(x)=2x^2+5x-1 | | (6x+3)-(-2x+9)= | | -4(t-4)-(t+3)=3 | | 0.16y+0.04(y+8000)=1920 | | m+m+7=19 | | (6x+3)-(2x+9)= | | n+6=-4n-14 | | 8(x-6)=32-8x | | -[8z-(18z+7)]=7+(9z+0) | | 7x+7=x | | 2x*2-30=4x | | 15p-5(6-5p)=5(p-6)-25 | | 3x*2-6x=-3 | | w+5w+5=50 | | -8(x+2)+4x+7=5x+11 | | 39-2n=-7(1-6n)+2n | | 0.7x+0.1(1-x)=0.2x+0.4(1-x) | | w+5w+z=50 |

Equations solver categories